MENINGKATKAN KEMAMPUAN PENGUCAPAN KONSONAN (S) MELALUI METODE MOTOKINESTETIK BAGI ANAK TUNAWICARA KELAS I DI SDN 35 PADANG SARAI - Yovi Meutia Putri, Mega Iswari, Zumiyetri (Universitas Negeri Padang, 2013)
This research is motivated tunawicara child class in SDN 35 Padang Sarai who have problems in pronouncing consonants including consonant (s), it is seen when researchers observed daily activities at school and at home. This study uses the Single Subject Research A-B design and data analysis techniques using Visual Graph Analysis. In the baseline condition pronunciation skills (s) that is 0% at the beginning of the word, consonant (s) in the middle of 0%, and the consonant (s) at the end lies in the range 0% to 40%. On pronunciation skills intervention condition (s) at the beginning of 20% to 100%, consonant (s) in the middle 20% to 80%, pronunciation (s) at the end of 80% to 100%. Based on these results we can conclude motokinestetik method can improve the ability of consonant pronunciation (s) of children tunawicara.